Waterproof wear-resistant fiber and preparation method thereof

Through modified polyester melt electrospinning and surface treatment technology, combined with the reaction of nano titanium dioxide and metaloporphyrin, waterproof and wear-resistant fibers are produced, which solves the problem of insufficient performance of existing textile materials and realizes waterproof and antibacterial of the fibers , flame retardant, anti-aging and wear resistance improvement.

CN119145081AInactive Publication Date: 2024-12-17JIANGSU RUI AIFU TEXTILE TECH CO LTD

Patent Information

Application Number
CN202411639479.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing textile materials are difficult to have the functions of waterproof, antibacterial, flame retardant, anti-aging and wear resistance, and cannot meet the market's demand for high-performance textiles.

Method used

The surface treatment is carried out by electrospinning of modified polyester melt, and waterproof and wear-resistant fibers are prepared by the reaction of chlorinated polyester, chlorinated nanotitanium dioxide, modified aminomethylporphyrin and other materials, and the physics of nanotitanium dioxide is used. Adsorporphyrin photocatalytic action, combined with the flame retardant mechanism of hydrogen fluoride, enhances the performance of fibers.

Benefits of technology

The fiber has been improved in waterproof, antibacterial, flame retardant, anti-aging and wear resistance, significantly improving the comprehensive performance of the material, and meeting the needs of high-performance textiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a waterproof wear-resistant fiber and a preparation method thereof, and relates to the field of fibers. When the waterproof wear-resistant fiber is prepared, p-nitrobenzaldehyde sequentially reacts with pyrrole, hydrogen, zinc acetate and 2, 5-dihydroxy terephthalaldehyde to prepare modified aminated metalloporphyrin; the preparation method comprises the following steps: carrying out a reaction on nano titanium dioxide and 3-chloropropyltrimethoxysilane to prepare chlorinated nano titanium dioxide; the preparation method comprises the following steps: reacting dimethyl terephthalate, 2-methyl-1, 4-butanediol and phenyl dichlorophosphine to prepare pre-modified polyester; enabling the pre-modified polyester to react with 1, 4-dichloromethoxybutane, so as to obtain chlorinated polyester; enabling chlorinated polyester, chlorinated nano titanium dioxide and modified aminated metalloporphyrin to react to prepare modified polyester; the modified polyester melt is subjected to electrostatic spinning and then immersed in a surface treatment solution to be subjected to surface treatment, and the waterproof wear-resistant fiber is prepared. The waterproof wear-resistant fiber prepared by the invention has excellent antibacterial, oil photocatalytic degradation, flame-retardant and anti-aging effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fibers, in particular to a waterproof and wear-resistant fiber and a preparation method thereof. Background Art

[0002] As the main product of chemical fiber, polyester accounts for a high proportion of chemical fiber output. The polyester industry is a basic industry related to the national economy and people's livelihood, and is a pillar industry of the national economy. Its products are widely used in chemical fiber, light industry, national defense, construction and other aspects. Polyester far exceeds other chemical fiber varieties in production capacity and technical level. Its low processing cost and high cost performance have led to a rapid increase in polyester production. Coupled with the industrialization of new products and new technologies, polyester has become the most consumed product among chemical fibers.

[0003] In the development and production of new textile materials in the future, polyester will become a top priority. With the continuous improvement of people's quality of life and the continuous progress of the textile industry, some basic functions of traditional textiles can no longer meet people's needs, and various functional textiles have received widespread attention. People's requirements for the wearing performance of fabrics are also getting higher and higher. At present, the market demand for fabrics with waterproof functions is increasing. This article introduces a waterproof and wear-resistant fiber with antibacterial, photocatalytic degradation of oils and fats, flame retardancy and anti-aging capabilities. Summary of the invention

[0004] The purpose of the present invention is to provide a waterproof and wear-resistant fiber and a preparation method thereof to solve the problems existing in the prior art.

[0005] A waterproof and wear-resistant fiber, which is prepared by electrostatic spinning of a modified polyester melt and then immersing it in a surface treatment liquid for surface treatment; The modified polyester is prepared by reacting chlorinated polyester, chlorinated nano-titanium dioxide and modified amino metal porphyrin; The chlorinated polyester is prepared by reacting dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine to obtain a pre-modified polyester; and reacting the pre-modified polyester with 1,4-dichloromethoxybutane to obtain the chlorinated polyester. The chlorinated nano titanium dioxide is prepared by reacting nano titanium dioxide and 3-chloropropyltrimethoxysilane; The modified aminated metal porphyrin is prepared by first reacting p-nitrobenzaldehyde with pyrrole and then with hydrogen to obtain the aminated porphyrin; the aminated porphyrin is first reacted with zinc acetate and then with 2,5-dihydroxyterephthalaldehyde to obtain the modified metal porphyrin.

[0006] A method for preparing a waterproof and wear-resistant fiber, the method for preparing the waterproof and wear-resistant fiber mainly comprises the following preparation steps: (1) The p-nitrobenzaldehyde mixed solution is heated to 130-150°C, and a pyrrole mixed solution of 0.24-0.26 times the mass of the p-nitrobenzaldehyde mixed solution is added at a constant speed of 200-300 r / min within 25-35 minutes, and the stirring is continued for 100-140 minutes. Ethanol of 1.2-1.3 times the mass of the p-nitrobenzaldehyde mixed solution is added, and the mixture is allowed to stand at 2-6°C for 22-24 hours, filtered, washed with ethanol for 3-5 times, and dried at 70-80°C for 4-6 hours to obtain nitrated porphyrin; the nitrated porphyrin is mixed with platinum in a mass ratio of 1:0.03-0.05, and hydrogen is introduced at 250-270°C for 8-10 hours to obtain amino porphyrin; (2) The amino porphyrin and dimethylformamide are mixed in a mass ratio of 3.5-4.5:1, and zinc acetate in an amount of 2-3 times the mass of the amino porphyrin is uniformly added at 200-300 r / min and 160-170°C within 25-35 minutes, and stirring is continued for 100-140 minutes. Deionized water in an amount of 3-5 times the mass of the amino porphyrin is added, and the mixture is allowed to stand at 2-6°C for 22-24 hours, filtered, and vacuum dried at -10-0°C for 22-26 hours to obtain amino metal porphyrin; the amino metal porphyrin, 2,5-dihydroxyterephthalaldehyde and ethanol are uniformly mixed in a molar ratio of 1:0.8-0.9:10-12, allowed to stand for 20-30 minutes, and dried at 70-80°C for 5-7 hours to obtain modified amino metal porphyrin; (3) Dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine are mixed uniformly in a molar ratio of 3-5:4-6:1, and then 0.01-0.02 times the mass of dimethyl terephthalate of aluminum chloride is added, and stirred for 10-12 hours at 210-220°C, 200-300 r / min, and under nitrogen protection to obtain pre-modified polyester; pre-modified polyester, 1,4-dichloromethoxybutane, dichloromethane and tin chloride are mixed in a mass ratio of 1:0.2-0.3:5-7:0.03-0.05, stirred at 200-300 r / min for 7-9 hours, dried at 30-40°C for 5-7 hours, washed with deionized water for 3-5 times, and vacuum dried at -10-0°C for 22-24 hours to obtain chlorinated polyester; (4) mixing chlorinated polyester, chlorinated nano-titanium dioxide, modified amino metal porphyrin and ethanol in a mass ratio of 8-10:0.8-1.2:2-4:16-20, stirring at 200-300 r / min for 20-40 min, and drying at 70-80°C for 5-7 h to obtain modified polyester; (5) The modified polyester is subjected to melt electrospinning, allowed to stand at 90-100°C for 6-8 hours, and naturally cooled to room temperature to obtain modified polyester fibers; the modified polyester fibers are immersed in a surface treatment solution, placed in a closed photoreactor, irradiated with a 40W purple LED light with a wavelength of 370nm at room temperature for 48-50 hours, taken out, immersed in deionized water for ultrasonic treatment for 10-20 minutes, and vacuum dried at -10--1°C for 22-24 hours to obtain waterproof and wear-resistant fibers.

[0007] As an optimization, the p-nitrobenzaldehyde mixed solution in step (1) is prepared by uniformly mixing propionic acid and p-nitrobenzaldehyde in a mass ratio of 9 to 11:1.

[0008] As an optimization, the pyrrole mixed solution in step (1) is prepared by uniformly mixing propionic acid and pyrrole in a mass ratio of 1:0.6-0.7.

[0009] As an optimization, the chlorinated nano-titanium dioxide in step (4) is prepared by uniformly mixing nano-titanium dioxide, 3-chloropropyltrimethoxysilane and isopropanol in a mass ratio of 1:1:6-8, stirring at 85-95°C and 200-300 r / min for 5-7 hours, centrifuging to obtain a solid, washing it with deionized water for 3-5 times, and drying it at 90-100°C for 2-4 hours.

[0010] As an optimization, the melt electrospinning parameters in step (5) are as follows: spinning temperature 260-280°C, discharge diameter 0.8-1.2 mm, spinning voltage 26-30 KV, and receiving distance 16-18 cm.

[0011] As an optimization, the surface treatment liquid in step (5) is prepared by uniformly mixing benzophenone, acetonitrile and N-(trifluoromethylthio)phthalimide in a mass ratio of 1:0.08-0.12:7-8 under nitrogen protection.

[0012] As an optimization, the preparation process of the amino porphyrin in step (1) is as follows:

[0013]

[0014] As an optimization, the preparation process of the modified amino metalloporphyrin in step (2) is as follows:

[0015]

[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the waterproof and wear-resistant fiber, the present invention sequentially reacts p-nitrobenzaldehyde with pyrrole, hydrogen, zinc acetate and 2,5-dihydroxyterephthalaldehyde to obtain modified amino metal porphyrin; reacts nano titanium dioxide and 3-chloropropyltrimethoxysilane to obtain chlorinated nano titanium dioxide; reacts dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyldichlorophosphine to obtain pre-modified polyester; reacts the pre-modified polyester with 1,4-dichloromethoxybutane to obtain chlorinated polyester; reacts chlorinated polyester, chlorinated nano titanium dioxide and modified amino metal porphyrin to obtain modified polyester; and electrostatically spins the modified polyester melt, immerses it in a surface treatment liquid, and performs surface treatment to obtain the waterproof and wear-resistant fiber.

[0017] First, p-nitrobenzaldehyde is reacted with pyrrole, hydrogen, zinc acetate and 2,5-dihydroxyterephthalaldehyde in sequence to obtain modified aminated metal porphyrin; metal porphyrin can decompose oil under photocatalysis and catalyze oil produced by human body under light; metal porphyrin can release zinc ions, which can interact with negative ions of bacterial cells to cause abnormal enzymes and other protein mechanisms in bacterial cells, thereby destroying their biofilm and metabolic basis. In addition, zinc ions can affect bacterial DNA replication and transcription, hinder their growth and reproduction, and achieve the effect of inhibiting and killing bacteria; aminated metal porphyrin can decompose and produce non-flammable gas after absorbing heat, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of polymers on the one hand, and the nitrogen oxides produced by decomposition can capture free radicals, inhibit the chain reaction of polymers, and improve the flame retardant ability of materials; the amino groups on the surface of aminated metal porphyrin react with aldehyde groups to form Schiff base structures, which interact with hydroxyl groups on the surface of benzene rings to achieve ultraviolet absorption ability, thereby achieving anti-aging effect.

[0018] Secondly, nano titanium dioxide and 3-chloropropyltrimethoxysilane are reacted to obtain chlorinated nano titanium dioxide; dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyldichlorophosphine are reacted to obtain pre-modified polyester; titanium dioxide has a high specific surface area and can effectively adsorb and fix microorganisms on the surface. This physical adsorption can prevent the normal growth and reproduction of microorganisms, thereby achieving the purpose of antibacterial. In addition, titanium dioxide can also interfere with the growth cycle of bacteria, destroy its biofilm structure, and further inhibit the growth and reproduction of bacteria, thereby achieving the effect of inhibiting and killing bacteria; and nano titanium dioxide can also enhance the wear resistance and Enhance the photocatalytic decomposition effect of metal porphyrin in grease; the polyester main chain contains phosphorus, and organic phosphorus can produce phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction and thus slow down the combustion, and can generate polymetaphosphoric acid with stable structure and non-volatile in the combustion process. Polymetaphosphoric acid has a strong dehydration effect, and during the heating process, it promotes the carbonization of the polymer into a dense and flame-retardant carbonized layer. The carbonized layer covers the surface of the polymer, isolating the bottom material from contact with external oxygen and hindering the transfer of external heat to the base material, thereby effectively preventing the material from further pyrolysis and terminating the combustion of the material, thereby improving the flame retardant ability of the material.

[0019] Finally, the pre-modified polyester is reacted with 1,4-dichloromethoxybutane to obtain chlorinated polyester; the chlorinated polyester, chlorinated nano-titanium dioxide and modified amino metal porphyrin are reacted to obtain modified polyester; the modified polyester melt is electrostatically spun and then immersed in a surface treatment liquid for surface treatment to obtain a waterproof and wear-resistant fiber; the pre-modified polyester is reacted with 1,4-dichloromethoxybutane to allow chlorine to be contained on the benzene of the polyester main chain; when preparing the modified amino metal porphyrin, the amino metal porphyrin is controlled to be excessive so that the surface of the modified amino metal porphyrin contains some unreacted amino groups, so as to achieve a better combination effect with the subsequent chlorinated nano-titanium dioxide and chlorinated polyester. The fiber surface treated with the surface treatment liquid is rich in fluorine, which can reduce the surface free energy and reduce the contact ability of the surface with other substances, thereby achieving a waterproof effect; it can also decompose when a fire occurs to produce hydrogen fluoride gas, which can react with the free radicals in the flame to replace hydrogen atoms, thereby destroying the flame chain reaction and slowing down or inhibiting the spread of the flame. In addition, hydrogen fluoride can also form hydrofluoric acid with hydrogen atoms, which reduces the burning rate of the flame and has a flame retardant effect. It can also form a protective film on the surface to prevent further contact between oxygen and fuel, slow down the spread of the flame, and improve the flame retardant ability of the material. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1

[0021] A method for preparing waterproof and wear-resistant fiber mainly comprises the following preparation steps: (1) The p-nitrobenzaldehyde mixture was heated to 130°C, and a pyrrole mixture of 0.24 times the mass of the p-nitrobenzaldehyde mixture was added at a constant speed of 200 r / min over 25 minutes. The mixture was stirred for 100 minutes, and ethanol of 1.2 times the mass of the p-nitrobenzaldehyde mixture was added. The mixture was allowed to stand at 2°C for 22 hours, filtered, washed with ethanol three times, and dried at 70°C for 4 hours to obtain nitrated porphyrin; the nitrated porphyrin was mixed with platinum in a mass ratio of 1:0.03, hydrogen was introduced at 250°C, and the mixture was reacted for 8 hours to obtain amino porphyrin; (2) Aminated porphyrin and dimethylformamide were mixed in a mass ratio of 3.5:1, and zinc acetate twice the mass of the amino porphyrin was added at a uniform rate at 200 r / min and 160°C for 25 minutes. Stirring was continued for 100 minutes, and deionized water three times the mass of the amino porphyrin was added. The mixture was allowed to stand at 2°C for 22 hours, filtered, and vacuum dried at -10°C for 22 hours to obtain amino metal porphyrin; Aminated metal porphyrin, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed uniformly in a molar ratio of 1:0.8:10, allowed to stand for 20 minutes, and dried at 70°C for 5 hours to obtain modified amino metal porphyrin; (3) Dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine were mixed uniformly in a molar ratio of 3:4:1, and then 0.01 times the mass of dimethyl terephthalate of aluminum chloride was added, and stirred for 10 hours at 210°C, 200 r / min, and under nitrogen protection to obtain a pre-modified polyester; the pre-modified polyester, 1,4-dichloromethoxybutane, dichloromethane and tin chloride were mixed in a mass ratio of 1:0.2:5:0.03, stirred at 200 r / min for 7 hours, dried at 30°C for 5 hours, washed with deionized water 3 times, and vacuum dried at -10°C for 22 hours to obtain a chlorinated polyester; (4) mixing chlorinated polyester, chlorinated nano-titanium dioxide, modified amino metal porphyrin and ethanol in a mass ratio of 8:0.8:2:16, stirring at 200 r / min for 20 min, and drying at 70°C for 5 h to obtain modified polyester; (5) The modified polyester was subjected to melt electrospinning, allowed to stand at 90°C for 6 hours, and naturally cooled to room temperature to obtain modified polyester fibers; the modified polyester fibers were immersed in a surface treatment solution, placed in a closed photoreactor, irradiated with a 40W purple LED light with a wavelength of 370nm at room temperature for 48 hours, taken out, immersed in deionized water for 10 minutes, and vacuum dried at -10°C for 22 hours to obtain waterproof and wear-resistant fibers. Example 2

[0022] A method for preparing waterproof and wear-resistant fiber mainly comprises the following preparation steps: (1) The p-nitrobenzaldehyde mixture was heated to 140°C, and a pyrrole mixture of 0.25 times the mass of the p-nitrobenzaldehyde mixture was added at a constant speed of 250 r / min within 30 minutes. The mixture was stirred for 120 minutes, and ethanol of 1.25 times the mass of the p-nitrobenzaldehyde mixture was added. The mixture was allowed to stand at 4°C for 23 hours, filtered, washed with ethanol 4 times, and dried at 75°C for 5 hours to obtain nitrated porphyrin; the nitrated porphyrin was mixed with platinum in a mass ratio of 1:0.04, hydrogen was introduced at 260°C, and the mixture was reacted for 9 hours to obtain amino porphyrin; (2) The amino porphyrin and dimethylformamide were mixed in a mass ratio of 4:1, and zinc acetate 2.5 times the mass of the amino porphyrin was added at a uniform rate at 250 r / min and 165°C for 30 minutes. The stirring was continued for 120 minutes, and deionized water 4 times the mass of the amino porphyrin was added. The mixture was allowed to stand at 4°C for 23 hours, filtered, and vacuum dried at -5°C for 24 hours to obtain amino metal porphyrin; the amino metal porphyrin, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed uniformly in a molar ratio of 1:0.85:11, allowed to stand for 25 minutes, and dried at 75°C for 6 hours to obtain modified amino metal porphyrin; (3) Dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine were mixed uniformly in a molar ratio of 4:5:1, and then 0.015 times the mass of aluminum chloride of dimethyl terephthalate was added, and stirred for 11 hours at 215°C, 250 r / min, and under nitrogen protection to obtain pre-modified polyester; pre-modified polyester, 1,4-dichloromethoxybutane, dichloromethane and tin chloride were mixed in a mass ratio of 1:0.25:6:0.04, stirred at 250 r / min for 8 hours, dried at 35°C for 6 hours, washed with deionized water 4 times, and vacuum dried at -5°C for 23 hours to obtain chlorinated polyester; (4) mixing chlorinated polyester, chlorinated nano-titanium dioxide, modified amino metal porphyrin and ethanol in a mass ratio of 9:1:3:18, stirring at 250 r / min for 30 min, and drying at 75°C for 6 h to obtain modified polyester; (5) The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain modified polyester fibers; the modified polyester fibers were immersed in a surface treatment solution, placed in a closed photoreactor, irradiated with a 40W purple LED light with a wavelength of 370nm at room temperature for 49 hours, taken out, immersed in deionized water for 15 minutes, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and wear-resistant fibers. Example 3

[0023] A method for preparing waterproof and wear-resistant fiber mainly comprises the following preparation steps: (1) The p-nitrobenzaldehyde mixture was heated to 150°C, and a pyrrole mixture of 0.26 times the mass of the p-nitrobenzaldehyde mixture was added at a constant speed of 300 r / min within 35 minutes. The mixture was stirred for 140 minutes, and ethanol of 1.3 times the mass of the p-nitrobenzaldehyde mixture was added. The mixture was allowed to stand at 6°C for 24 hours, filtered, washed with ethanol for 5 times, and dried at 80°C for 6 hours to obtain nitrated porphyrin; the nitrated porphyrin was mixed with platinum in a mass ratio of 1:0.05, hydrogen was introduced at 270°C, and the mixture was reacted for 10 hours to obtain amino porphyrin; (2) The amino porphyrin and dimethylformamide were mixed in a mass ratio of 4.5:1, and zinc acetate 3 times the mass of the amino porphyrin was uniformly added at 300 r / min and 170°C for 35 minutes. Stirring was continued for 140 minutes, and deionized water 5 times the mass of the amino porphyrin was added. The mixture was allowed to stand at 6°C for 24 hours, filtered, and vacuum dried at 0°C for 26 hours to obtain amino metal porphyrin; the amino metal porphyrin, 2,5-dihydroxyterephthalaldehyde and ethanol were uniformly mixed in a molar ratio of 1:0.9:12, allowed to stand for 30 minutes, and dried at 80°C for 7 hours to obtain modified amino metal porphyrin; (2) Dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine were mixed uniformly in a molar ratio of 5:6:1, and then 0.02 times the mass of dimethyl terephthalate of aluminum chloride was added, and stirred for 12 hours at 220°C, 300 r / min, and under nitrogen protection to obtain a pre-modified polyester; the pre-modified polyester, 1,4-dichloromethoxybutane, dichloromethane and tin chloride were mixed in a mass ratio of 1:0.3:7:0.05, stirred at 300 r / min for 9 hours, dried at 40°C for 7 hours, washed with deionized water 5 times, and vacuum dried at 0°C for 24 hours to obtain a chlorinated polyester; (3) mixing chlorinated polyester, chlorinated nano-titanium dioxide, modified amino metal porphyrin and ethanol in a mass ratio of 10:1.2:4:20, stirring at 300 r / min for 40 min, and drying at 80°C for 7 h to obtain modified polyester; (4) The modified polyester was subjected to melt electrospinning, allowed to stand at 100°C for 8 hours, and naturally cooled to room temperature to obtain modified polyester fibers; the modified polyester fibers were immersed in a surface treatment solution, placed in a closed photoreactor, irradiated with a 40W purple LED light with a wavelength of 370nm at room temperature for 50 hours, taken out, immersed in deionized water for ultrasonic treatment for 20 minutes, and vacuum dried at -1°C for 24 hours to obtain waterproof and wear-resistant fibers.

[0024] Comparative Example 1 A method for preparing waterproof and wear-resistant fiber mainly comprises the following preparation steps: (1) The p-nitrobenzaldehyde mixture was heated to 140°C, and a pyrrole mixture of 0.25 times the mass of the p-nitrobenzaldehyde mixture was added at a constant speed of 250 r / min within 30 minutes. The mixture was stirred for 120 minutes, and ethanol of 1.25 times the mass of the p-nitrobenzaldehyde mixture was added. The mixture was allowed to stand at 4°C for 23 hours, filtered, washed with ethanol 4 times, and dried at 75°C for 5 hours to obtain nitrated porphyrin; the nitrated porphyrin was mixed with platinum in a mass ratio of 1:0.04, hydrogen was introduced at 260°C, and the mixture was reacted for 9 hours to obtain amino porphyrin; (2) The amino porphyrin and dimethylformamide were mixed in a mass ratio of 4:1, and zinc acetate (2.5 times the mass of the amino porphyrin) was added at a constant rate of 250 r / min and 165°C for 30 min. The stirring was continued for 120 min, and deionized water (4 times the mass of the amino porphyrin) was added. The mixture was allowed to stand at 4°C for 23 h, filtered, and vacuum dried at -5°C for 24 h to obtain the amino metal porphyrin. (3) Dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine were mixed uniformly in a molar ratio of 4:5:1, and then 0.015 times the mass of aluminum chloride of dimethyl terephthalate was added, and stirred for 11 hours at 215°C, 250 r / min, and under nitrogen protection to obtain pre-modified polyester; pre-modified polyester, 1,4-dichloromethoxybutane, dichloromethane and tin chloride were mixed in a mass ratio of 1:0.25:6:0.04, stirred at 250 r / min for 8 hours, dried at 35°C for 6 hours, washed with deionized water 4 times, and vacuum dried at -5°C for 23 hours to obtain chlorinated polyester; (4) mixing chlorinated polyester, chlorinated nano-titanium dioxide, amino metal porphyrin and ethanol in a mass ratio of 9:1:3:18, stirring at 250 r / min for 30 min, and drying at 75°C for 6 h to obtain modified polyester; (5) The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain modified polyester fibers; the modified polyester fibers were immersed in a surface treatment solution, placed in a closed photoreactor, irradiated with a 40W purple LED light with a wavelength of 370nm at room temperature for 49 hours, taken out, immersed in deionized water for 15 minutes, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and wear-resistant fibers.

[0025] Comparative Example 2 A method for preparing waterproof and wear-resistant fiber mainly comprises the following preparation steps: (1) Dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine were mixed uniformly in a molar ratio of 4:5:1, and then 0.015 times the mass of aluminum chloride of dimethyl terephthalate was added, and stirred for 11 hours at 215°C, 250 r / min, and under nitrogen protection to obtain a pre-modified polyester; the pre-modified polyester, 1,4-dichloromethoxybutane, dichloromethane and tin chloride were mixed in a mass ratio of 1:0.25:6:0.04, stirred at 250 r / min for 8 hours, dried at 35°C for 6 hours, washed with deionized water for 4 times, and vacuum dried at -5°C for 23 hours to obtain a chlorinated polyester; (2) mixing chlorinated polyester, chlorinated nano-titanium dioxide and ethanol in a mass ratio of 9:1:18, stirring at 250 r / min for 30 min, and drying at 75°C for 6 h to obtain modified polyester; (3) The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain modified polyester fibers; the modified polyester fibers were immersed in a surface treatment solution, placed in a closed photoreactor, irradiated with a 40W purple LED light with a wavelength of 370nm at room temperature for 49 hours, taken out, immersed in deionized water for 15 minutes, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and wear-resistant fibers.

[0026] Comparative Example 3 A method for preparing waterproof and wear-resistant fiber mainly comprises the following preparation steps: (1) The p-nitrobenzaldehyde mixture was heated to 140°C, and a pyrrole mixture of 0.25 times the mass of the p-nitrobenzaldehyde mixture was added at a constant speed of 250 r / min within 30 minutes. The mixture was stirred for 120 minutes, and ethanol of 1.25 times the mass of the p-nitrobenzaldehyde mixture was added. The mixture was allowed to stand at 4°C for 23 hours, filtered, washed with ethanol 4 times, and dried at 75°C for 5 hours to obtain nitrated porphyrin; the nitrated porphyrin was mixed with platinum in a mass ratio of 1:0.04, hydrogen was introduced at 260°C, and the mixture was reacted for 9 hours to obtain amino porphyrin; (2) The amino porphyrin and dimethylformamide were mixed in a mass ratio of 4:1, and zinc acetate 2.5 times the mass of the amino porphyrin was added at a uniform rate at 250 r / min and 165°C for 30 minutes. The stirring was continued for 120 minutes, and deionized water 4 times the mass of the amino porphyrin was added. The mixture was allowed to stand at 4°C for 23 hours, filtered, and vacuum dried at -5°C for 24 hours to obtain amino metal porphyrin; the amino metal porphyrin, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed uniformly in a molar ratio of 1:0.85:11, allowed to stand for 25 minutes, and dried at 75°C for 6 hours to obtain modified amino metal porphyrin; (3) Dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine were mixed uniformly in a molar ratio of 4:5:1, and then 0.015 times the mass of aluminum chloride of dimethyl terephthalate was added, and stirred for 11 hours at 215°C, 250 r / min, and under nitrogen protection to obtain pre-modified polyester; pre-modified polyester, 1,4-dichloromethoxybutane, dichloromethane and tin chloride were mixed in a mass ratio of 1:0.25:6:0.04, stirred at 250 r / min for 8 hours, dried at 35°C for 6 hours, washed with deionized water 4 times, and vacuum dried at -5°C for 23 hours to obtain chlorinated polyester; (4) mixing chlorinated polyester, modified amino metal porphyrin and ethanol in a mass ratio of 9:3:18, stirring at 250 r / min for 30 min, and drying at 75° C. for 6 h to obtain modified polyester; (5) The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain modified polyester fibers; the modified polyester fibers were immersed in a surface treatment solution, placed in a closed photoreactor, irradiated with a 40W purple LED light with a wavelength of 370nm at room temperature for 49 hours, taken out, immersed in deionized water for 15 minutes, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and wear-resistant fibers.

[0027] Comparative Example 4 A method for preparing waterproof and wear-resistant fiber mainly comprises the following preparation steps: (1) The p-nitrobenzaldehyde mixture was heated to 140°C, and a pyrrole mixture of 0.25 times the mass of the p-nitrobenzaldehyde mixture was added at a constant speed of 250 r / min within 30 minutes. The mixture was stirred for 120 minutes, and ethanol of 1.25 times the mass of the p-nitrobenzaldehyde mixture was added. The mixture was allowed to stand at 4°C for 23 hours, filtered, washed with ethanol 4 times, and dried at 75°C for 5 hours to obtain nitrated porphyrin; the nitrated porphyrin was mixed with platinum in a mass ratio of 1:0.04, hydrogen was introduced at 260°C, and the mixture was reacted for 9 hours to obtain amino porphyrin; (2) The amino porphyrin and dimethylformamide were mixed in a mass ratio of 4:1, and zinc acetate 2.5 times the mass of the amino porphyrin was added at a uniform rate at 250 r / min and 165°C for 30 minutes. The stirring was continued for 120 minutes, and deionized water 4 times the mass of the amino porphyrin was added. The mixture was allowed to stand at 4°C for 23 hours, filtered, and vacuum dried at -5°C for 24 hours to obtain amino metal porphyrin; the amino metal porphyrin, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed uniformly in a molar ratio of 1:0.85:11, allowed to stand for 25 minutes, and dried at 75°C for 6 hours to obtain modified amino metal porphyrin; (3) Dimethyl terephthalate and 2-methyl-1,4-butanediol were mixed uniformly in a molar ratio of 4:5, and then 0.015 times the mass of aluminum chloride of dimethyl terephthalate was added, and stirred for 11 hours at 215°C, 250 r / min, and under nitrogen protection to obtain a pre-modified polyester; (4) Pre-modified polyester, chlorinated nano-titanium dioxide, modified amino metal porphyrin and ethanol were mixed in a mass ratio of 9:1:3:18, stirred at 250 r / min for 30 min, and dried at 75°C for 6 h to obtain modified polyester; (5) The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 hours, and naturally cooled to room temperature to obtain modified polyester fibers; the modified polyester fibers were immersed in a surface treatment solution, placed in a closed photoreactor, irradiated with a 40W purple LED light with a wavelength of 370nm at room temperature for 49 hours, taken out, immersed in deionized water for 15 minutes, and vacuum dried at -5.5°C for 23 hours to obtain waterproof and wear-resistant fibers.

[0028] Comparative Example 5 A method for preparing waterproof and wear-resistant fiber mainly comprises the following preparation steps: (1) The p-nitrobenzaldehyde mixture was heated to 140°C, and a pyrrole mixture of 0.25 times the mass of the p-nitrobenzaldehyde mixture was added at a constant speed of 250 r / min within 30 minutes. The mixture was stirred for 120 minutes, and ethanol of 1.25 times the mass of the p-nitrobenzaldehyde mixture was added. The mixture was allowed to stand at 4°C for 23 hours, filtered, washed with ethanol 4 times, and dried at 75°C for 5 hours to obtain nitrated porphyrin; the nitrated porphyrin was mixed with platinum in a mass ratio of 1:0.04, hydrogen was introduced at 260°C, and the mixture was reacted for 9 hours to obtain amino porphyrin; (2) The amino porphyrin and dimethylformamide were mixed in a mass ratio of 4:1, and zinc acetate 2.5 times the mass of the amino porphyrin was added at a uniform rate at 250 r / min and 165°C for 30 minutes. The stirring was continued for 120 minutes, and deionized water 4 times the mass of the amino porphyrin was added. The mixture was allowed to stand at 4°C for 23 hours, filtered, and vacuum dried at -5°C for 24 hours to obtain amino metal porphyrin; the amino metal porphyrin, 2,5-dihydroxyterephthalaldehyde and ethanol were mixed uniformly in a molar ratio of 1:0.85:11, allowed to stand for 25 minutes, and dried at 75°C for 6 hours to obtain modified amino metal porphyrin; (3) Dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine were mixed uniformly in a molar ratio of 4:5:1, and then 0.015 times the mass of aluminum chloride of dimethyl terephthalate was added, and stirred for 11 hours at 215°C, 250 r / min, and under nitrogen protection to obtain pre-modified polyester; pre-modified polyester, 1,4-dichloromethoxybutane, dichloromethane and tin chloride were mixed in a mass ratio of 1:0.25:6:0.04, stirred at 250 r / min for 8 hours, dried at 35°C for 6 hours, washed with deionized water 4 times, and vacuum dried at -5°C for 23 hours to obtain chlorinated polyester; (4) mixing chlorinated polyester, chlorinated nano-titanium dioxide, modified amino metal porphyrin and ethanol in a mass ratio of 9:1:3:18, stirring at 250 r / min for 30 min, and drying at 75°C for 6 h to obtain modified polyester; (5) The modified polyester was subjected to melt electrospinning, allowed to stand at 95°C for 7 h, and naturally cooled to room temperature to obtain modified polyester fibers.

[0029] Test Example 1 Flame retardancy test The limiting oxygen index was tested according to GBT / 2406 test standard. The results are shown in Table 1.

[0030] Table 1

[0031] From the comparison of the experimental data in Table 1, it can be found that the waterproof and corrosion-resistant fabric prepared by the present invention has good flame retardancy.

[0032] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 2, which shows that the metal porphyrin can decompose to produce non-combustible gas after absorbing heat, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of the polymer on the one hand, and the nitrogen oxides produced by decomposition can capture free radicals on the other hand, inhibit the chain reaction of the polymer, improve the flame retardancy of the material, and increase the limiting oxygen index of the material; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 4, which shows that the organic phosphorus can produce phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction to slow down the combustion, and can generate polymetaphosphoric acid with stable structure and non-volatile in the combustion process. Polymetaphosphoric acid has a strong dehydration effect, which promotes the carbonization of the polymer into a dense and flame-retardant carbonized layer during the heating process. The carbonized layer covers the surface of the polymer, isolates the bottom material from the contact with the external oxygen, and hinders the external heat from being transferred to the base material, thereby effectively preventing the material from further pyrolysis and terminating the combustion of the material, improving the flame retardancy of the material, and increasing the limiting oxygen index of the material; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 5, which indicates that the fiber surface treated with the surface treatment liquid is rich in fluorine and will decompose when a fire occurs to produce hydrogen fluoride gas. The hydrogen fluoride gas can react with the free radicals in the flame to replace hydrogen atoms, thereby destroying the flame chain reaction and slowing down or inhibiting the spread of the flame. In addition, hydrogen fluoride can also form hydrofluoric acid with hydrogen atoms, which reduces the combustion rate of the flame and has a flame retardant effect. It can also form a protective film on the surface to prevent further contact between oxygen and fuel, slow down the spread of the flame, improve the flame retardant ability of the material, and increase the limiting oxygen index of the material.

[0033] Test Example 2 Antimicrobial testing The test was carried out according to the GB / T20944 oscillation method, wherein the selected bacteria species were Staphylococcus aureus and Escherichia coli. The results are shown in Table 2.

[0034] Table 2

[0035] From the comparison of the experimental data in Table 2, it can be found that the waterproof and corrosion-resistant fabric prepared by the present invention has good antibacterial ability.

[0036] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 2, it can be found that the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 2, indicating that metalloporphyrins can release zinc ions, and zinc ions can interact with the negative ions of bacterial cells to cause abnormal enzymes and other protein mechanisms in bacterial cells, thereby destroying their biofilms and metabolic basis. In addition, zinc ions can affect bacterial DNA replication and transcription, hinder their growth and reproduction, and achieve the effect of inhibiting and killing bacteria. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 3, which shows that titanium dioxide has a higher specific surface area and can effectively adsorb and fix microorganisms on the surface. This physical adsorption can prevent the normal growth and reproduction of microorganisms, thereby achieving the antibacterial purpose. In addition, titanium dioxide can also interfere with the growth cycle of bacteria, destroy its biofilm structure, and further inhibit the growth and reproduction of bacteria, thereby achieving the effect of inhibiting and killing bacteria.

[0037] Test Example 3 Waterproof test Waterproof test: The water contact angle was measured using a contact angle meter. The results are shown in Table 3.

[0038] Table 3

[0039] From the comparison of the experimental data in Table 3, it can be found that the high-strength corrosion-resistant fiber prepared by the present invention has good waterproof ability.

[0040] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5 in Table 3, it can be found that the water contact angles of Examples 1, 2, 3 are larger than that of Comparative Example 5, which indicates that the surface of the material can be enriched with fluorine after being treated with the surface treatment liquid, which can reduce the surface free energy and the contact ability of the surface with other substances, thereby achieving a waterproof effect.

[0041] Test Example 4 Anti-aging test Anti-aging test: The artificial accelerated light aging test was carried out according to ISO4892-3 international standard, using fluorescent ultraviolet lamp UV-A340. After 15 days of irradiation, the fiber tensile strength was tested using a YG061F electronic single yarn strength tester. The test standard was GB / T14344, and the tensile fracture retention rate was calculated, where the tensile fracture retention rate = tensile fracture strength after aging treatment / tensile fracture strength before aging treatment * 100%. The results are shown in Table 4.

[0042] Table 4

[0043] From the comparison of the experimental data in Table 4, it can be found that the anti-aging fiber prepared by the present invention has good anti-aging ability.

[0044] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 4, it can be found that the fracture retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 2, which indicates that the amino groups on the surface of the amino metal porphyrin react with the aldehyde groups to form a Schiff base structure, which interacts with the hydroxyl groups on the surface of the benzene ring to achieve the ability of ultraviolet absorption, thereby achieving an anti-aging effect and increasing the fracture retention rate of the material.

[0045] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the fracture retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 3, which shows that titanium dioxide has the ability to resist ultraviolet rays and has anti-aging effects, and can increase the fracture retention rate of the material.

[0046] Test Example 5 Wear test The test was conducted using a reciprocating fiber wear tester. The diameter of the friction roller was 10 mm, and the surface was covered with W20 (02) metallographic sandpaper. The abrasive material on the sandpaper surface was silicon carbide, and the corresponding abrasive size was 20 μm. The reciprocating distance was 25 mm, the reciprocating frequency was 95 times / min, and the fiber tension was 0.45 cN·dtex. -1 The fiber-coated friction roller has a coating angle of 110°, the test environment temperature is 25°C, and the humidity is 60%. The number of reciprocating times of the friction roller from the start of the fiber wear resistance test to the fiber wear and fracture failure is defined as the maximum friction number of the fiber. The results are shown in Table 5.

[0047] Table 5

[0048] From the comparison of the experimental data in Table 5, it can be found that the anti-aging fiber prepared by the present invention has good wear resistance.

[0049] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 5, it can be found that the fracture retention rates of Examples 1, 2, 3 are greater than that of Comparative Example 3, which indicates that nano-titanium dioxide can enhance the wear resistance of the fiber.

[0050] Test Example 6 Grease decomposition test 1g of triglyceride was evenly applied on the surface of 10g of fiber, placed under natural light for 24h, the fiber quality was tested, and the oil decomposition rate was calculated, where the oil decomposition rate = (fiber quality after natural light irradiation - 10) / 1 * 100%. The results are shown in Table 6.

[0051] Table 6

[0052] From the comparison of the experimental data in Table 6, it can be found that the anti-aging fiber prepared by the present invention has a good ability to photocatalytically decompose grease.

[0053] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 6, it can be found that the oil decomposition rate of Examples 1, 2, 3 is greater than that of Comparative Example 2, which shows that metal porphyrin can decompose oil under photocatalysis; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the oil decomposition rate of Examples 1, 2, 3 is greater than that of Comparative Example 3, which shows that titanium dioxide can enhance the effect of photocatalytic decomposition of oil by metal porphyrin.

[0054] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A waterproof and wear-resistant fiber, characterized in that: The waterproof and wear-resistant fiber is prepared by electrostatic spinning of a modified polyester melt and then immersing it in a surface treatment liquid for surface treatment; The modified polyester is prepared by reacting chlorinated polyester, chlorinated nano-titanium dioxide and modified amino metal porphyrin; The chlorinated polyester is prepared by reacting dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine to obtain a pre-modified polyester; and reacting the pre-modified polyester with 1,4-dichloromethoxybutane to obtain the chlorinated polyester. The chlorinated nano titanium dioxide is prepared by reacting nano titanium dioxide and 3-chloropropyltrimethoxysilane; The modified aminated metal porphyrin is prepared by first reacting p-nitrobenzaldehyde with pyrrole and then with hydrogen to obtain the aminated porphyrin; the aminated porphyrin is first reacted with zinc acetate and then with 2,5-dihydroxyterephthalaldehyde to obtain the modified metal porphyrin.

2. A method for preparing a waterproof and wear-resistant fiber, characterized in that: The preparation method of the waterproof and wear-resistant fiber mainly includes the following preparation steps: (1) The p-nitrobenzaldehyde mixed solution is heated to 130-150°C, and a pyrrole mixed solution of 0.24-0.26 times the mass of the p-nitrobenzaldehyde mixed solution is added at a constant speed of 200-300 r / min within 25-35 minutes, and the stirring is continued for 100-140 minutes. Ethanol of 1.2-1.3 times the mass of the p-nitrobenzaldehyde mixed solution is added, and the mixture is allowed to stand at 2-6°C for 22-24 hours, filtered, washed with ethanol for 3-5 times, and dried at 70-80°C for 4-6 hours to obtain nitrated porphyrin; the nitrated porphyrin is mixed with platinum in a mass ratio of 1:0.03-0.05, and hydrogen is introduced at 250-270°C for 8-10 hours to obtain amino porphyrin; (2) The amino porphyrin and dimethylformamide are mixed in a mass ratio of 3.5-4.5:1, and zinc acetate in an amount of 2-3 times the mass of the amino porphyrin is uniformly added at 200-300 r / min and 160-170°C within 25-35 minutes, and stirring is continued for 100-140 minutes. Deionized water in an amount of 3-5 times the mass of the amino porphyrin is added, and the mixture is allowed to stand at 2-6°C for 22-24 hours, filtered, and vacuum dried at -10-0°C for 22-26 hours to obtain amino metal porphyrin; the amino metal porphyrin, 2,5-dihydroxyterephthalaldehyde and ethanol are uniformly mixed in a molar ratio of 1:0.8-0.9:10-12, allowed to stand for 20-30 minutes, and dried at 70-80°C for 5-7 hours to obtain modified amino metal porphyrin; (3) Dimethyl terephthalate, 2-methyl-1,4-butanediol and phenyl dichlorophosphine are uniformly mixed in a molar ratio of 3-5:4-6:1, and then 0.01-0.02 times the mass of dimethyl terephthalate of aluminum chloride is added, and stirred for 10-12 hours at 210-220°C, 200-300 r / min, and under nitrogen protection to obtain a pre-modified polyester; The pre-modified polyester, 1,4-dichloromethoxybutane, dichloromethane and tin chloride are mixed in a mass ratio of 1:0.2-0.3:5-7:0.03-0.05, stirred at 200-300 r / min for 7-9 hours, dried at 30-40°C for 5-7 hours, washed with deionized water for 3-5 times, and vacuum dried at -10-0°C for 22-24 hours to obtain chlorinated polyester; (4) mixing chlorinated polyester, chlorinated nano-titanium dioxide, modified amino metal porphyrin and ethanol in a mass ratio of 8-10:0.8-1.2:2-4:16-20, stirring at 200-300 r / min for 20-40 min, and drying at 70-80°C for 5-7 h to obtain modified polyester; (5) The modified polyester is subjected to melt electrospinning, allowed to stand at 90-100°C for 6-8 hours, and naturally cooled to room temperature to obtain modified polyester fibers; the modified polyester fibers are immersed in a surface treatment solution, placed in a closed photoreactor, irradiated with a 40W purple LED light with a wavelength of 370nm at room temperature for 48-50 hours, taken out, immersed in deionized water for ultrasonic treatment for 10-20 minutes, and vacuum dried at -10--1°C for 22-24 hours to obtain waterproof and wear-resistant fibers.

3. The method for preparing a waterproof and wear-resistant fiber according to claim 2, characterized in that: The p-nitrobenzaldehyde mixed solution in step (1) is prepared by uniformly mixing propionic acid and p-nitrobenzaldehyde in a mass ratio of 9 to 11:

1.

4. The method for preparing a waterproof and wear-resistant fiber according to claim 2, characterized in that: The pyrrole mixed solution in step (1) is prepared by uniformly mixing propionic acid and pyrrole in a mass ratio of 1:0.6-0.

7.

5. The method for preparing a waterproof and wear-resistant fiber according to claim 2, characterized in that: The chlorinated nano titanium dioxide in step (4) is prepared by uniformly mixing nano titanium dioxide, 3-chloropropyltrimethoxysilane and isopropanol in a mass ratio of 1:1:6-8, stirring at 85-95°C and 200-300 r / min for 5-7 hours, centrifuging to obtain a solid, washing it with deionized water for 3-5 times, and drying it at 90-100°C for 2-4 hours.

6. The method for preparing a waterproof and wear-resistant fiber according to claim 2, characterized in that: The melt electrospinning parameters in step (5) are spinning temperature 260-280°C, discharge diameter 0.8-1.2 mm, spinning voltage 26-30 KV, and receiving distance 16-18 cm.

7. The method for preparing a waterproof and wear-resistant fiber according to claim 2, characterized in that: The surface treatment liquid in step (5) is prepared by uniformly mixing benzophenone, acetonitrile and N-(trifluoromethylthio)phthalimide in a mass ratio of 1:0.08-0.12:7-8 under nitrogen protection.

Citation Information

Patent Citations

  • High-fire-resistance industrial filaments applied to steamship mooring rope

    CN105297155A

  • Ligand-driven porphyrinyl covalent organic framework material stripping method

    CN115417960A

  • Production process of anti-static antibacterial textile fabric

    CN117779458A

  • High-flame-retardant high-toughness polyester as well as preparation method and application thereof

    CN118005901A

Cited By

  • Ultraviolet light absorption antistatic fabric and preparation method thereof

    CN119571519A

  • Wear-resistant toughened electronic cigarette oil guide rope and preparation method thereof

    CN120138975A